The Grading of Recommendations, assessment, development, and evaluation approach was rarely followed and inconsistently applied in pressure injury prevention guidelines development: A cross-sectional survey. Issue 3 (August 2022) - Chen, Zhonglan; He, Lingxiao; Liu, Shanshan; Liu, Huan; Yu, Jiajie; Li, Youping
Abstract: Introduction: The Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach was developed to assess the certainty (or quality) of evidence and strength of recommendations in guidelines and endorsed internationally as a standard. Some guidelines had been developed to promote pressure injury prevention. Aims: We explored whether and to what extent the development of pressure injury prevention guidelines had followed or been informed by the GRADE approach. If this approach was not used, we examined which other methods were used instead. Methods: A cross-sectional study of pressure injury prevention guidelines was conducted. PubMed, Embase, CINAHL, and Chinese databases as well as guideline repositories and websites of professional bodies were searched for guidelines from 1990 to 2020. The grading systems of the certainty (or quality) of evidence and strength of recommendations of included guidelines were extracted. For the GRADE approach guidelines, compliance was assessed with the GRADE application criteria. Results: Twenty guidelines were identified. Among them, four guidelines (20%) indicated the use of the GRADE approach. The compliance rate ranged from 33.3%–94.4%. Other approaches, such as the Scottish Intercollegiate Guidelines Network (SIGN) approach, were also used. Conclusion: The GRADE approach is rarely followed and inconsistently applied in pressure injury prevention guidelines. Other systems, such as the SIGN approach, are being used despite being outdated or inconsistent. Strategies for further uptake and appropriate application of the GRADE approach among guideline developers are needed in the future. Highlights: Inconsistency and variability was observed in the grading systems in PI prevention guidelines. The GRADE approach was rarely used and inconsistently followed. Some unified grading systems such as the GRADE approach should be encouraged in the development of guidelines.